Effect of rehydration on textural properties, oral behavior, kinetics and water state of textured wheat gluten. (15th May 2022) - Peng, Jing; Lu, Lu; Zhu, Ke-Xue; Guo, Xiao-Na; Chen, Yuan; Zhou, Hui-Ming
Highlights: Steam pretreatment shorten rehydration time from over 120 min to within 20 min. Weibull model was suitable for the rehydration kinetics of textured wheat gluten. Steam improved textural properties and decreased the rehydration loss ratio. EMG was used to monitor the oral behaviors of textured wheat gluten after rehydration. Steam pretreatment accelerated the diffusion of water and heat. Abstract: To reduce the rehydration time and improve the quality of textured wheat gluten (TWG), the effects of steam pretreatment and water temperature (45 °C, 65 °C, and 85 °C) on the rehydration of TWG were investigated. Four different models were used to describe the rehydration kinetics: Peleg, Weibull, first-order, and exponential association models, with the Weibull model found to give the best fit. High temperature induced deterioration of textural properties and oral processing behavior and increased the rehydration loss ratio, while steam pretreatment reduced these negative changes. Morphological results showed that the surface and cross-sectional structure were conducive to water diffusion with steam pretreatment. Low-field nuclear magnetic resonance and infrared thermal results indicated that steam pretreatment promoted the diffusion of water and reduced the time required to reach thermal equilibrium. This work provides a fast rehydration method for TWG to help in the future production of high-quality meat analogues.